Dependence of pedestal structure on collisionality at fixed beta in JT-60U. (25th November 2015) - Urano, H.; Aiba, N.; Kamiya, K.; Kamada, Y.
Abstract: The dependence of pedestal structure on collisionality at fixed beta has been investigated in JT-60U. In the ITER-relevant low collisionality regime, the pedestal width does not change with edge collisionality. In the high collisionality regime, the pedestal width broadens with increased edge collisionality. The pedestal pressure gradient and width are not significantly changed when the pedestal is close to an intermediate n peeling-ballooning mode boundary at low collisionality. The experimental result indicates that conventional pedestal models where the pedestal width is independent of collisionality and is determined by at the pedestal is not a bad assumption in the ITER-relevant low collisionality regime. On the other hand, the pressure gradient decreases and the pedestal width increases at high collisionality. The pedestal broadening becomes significant when the pedestal is marginal to be unstable at the high n ballooning mode in the high collisionality regime.